2018
DOI: 10.3390/nu10010039
|View full text |Cite
|
Sign up to set email alerts
|

Fat, Sugar, Whole Grains and Heart Disease: 50 Years of Confusion

Abstract: During the 1970s some investigators proposed that refined carbohydrates, especially sugar and a low intake of dietary fiber, were major factors in coronary heart disease (CHD). This suggestion was eclipsed by the belief that an excess intake of saturated fatty acids (SFA) was the key dietary factor, a view that prevailed from roughly 1974 to 2014. Findings that have accumulated since 1990 inform us that the role of SFA in the causation of CHD has been much exaggerated. A switch from SFA to refined carbohydrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 51 publications
1
55
0
2
Order By: Relevance
“…It was demonstrated that the replacement of fat intake with refined carbohydrate was associated with elevated blood lipids and blood pressure [46,47]. This is a particular concern as refined carbohydrates (added sugar and SSB) have been also linked to the risk of heart disease due to its large consumption [48,49]. Although it is quite natural to experience peaks in TC and LDL-C levels during adolescence, an elevated LDL-C during adolescence was a significant predictor for 38% of dyslipidaemia cases in adulthood [50].…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that the replacement of fat intake with refined carbohydrate was associated with elevated blood lipids and blood pressure [46,47]. This is a particular concern as refined carbohydrates (added sugar and SSB) have been also linked to the risk of heart disease due to its large consumption [48,49]. Although it is quite natural to experience peaks in TC and LDL-C levels during adolescence, an elevated LDL-C during adolescence was a significant predictor for 38% of dyslipidaemia cases in adulthood [50].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, research on children has failed to associate fat intake to the lipidemic profile in CF [ 38 ], whereas on the other hand, it had been suggested that the high prevalence of hypertriglyceridemia observed in CF might be associated with an increased carbohydrate intake, and not the result of the high-fat diet [ 45 ]. Nevertheless, recommendations regarding the intake of SFA in CF retain the former low recommended SFA intake values, despite the existing evidence controversy and scientific debate [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is quite natural to experience peaks in TC and LDL-C levels during adolescence, it was suggested that elevated LDL-C concentrations among adolescents aged 12 to 18 years was a significant predictor for 38% of dyslipidaemia cases in adulthood after 20 years of follow-up (44). While saturated fatty acids was hypothesised to be associated with the development of heart disease in early 1970s, decades later, refined carbohydrates (added sugar and SSB) have been also linked to the risk of heart disease due to its large consumption (45,46).…”
Section: Discussionmentioning
confidence: 99%